Traffic-related air pollution is a risk factor in the development of chronic obstructive pulmonary disease - Zheng, Jinzhen; Liu, Sha; Peng, Jieqi; Peng, Huanhuan; Wang, Zihui; Deng, Zhishan; Li, Chenglong; Li, Naijian; Tang, Longhui; Xu, Jianwu; Li, Jingwen; Li, Bing; et al. (Frontiers in Public Health, 2022)
Background Outdoor traffic-related air pollution has negative effects on respiratory health. In this study, we aimed to explore the effect of outdoor traffic-related air pollution on chronic obstructive pulmonary disease (COPD) in Guangzhou. Methods We enrolled 1,460 residents aged 40 years or older between 21 January 2014 and 31 January 2018. We administered questionnaires and spirometry tests. The distance of participants' residences or locations of outdoor activities from busy roads (as indicators of outdoor traffic-related air pollution), indoor air pollution, and smoking history were queried in the questionnaires. Results Of the 1,460 residents with valid survey and test results, 292 were diagnosed with COPD, with a detection rate of 20%. Participants who lived and did their outdoor activities near busy roads had a higher detection rate of COPD. Among residents living at distances of <50 meters, 50–199 meters, and more than 200 meters from busy roads, the detection rates were 20.6, 21.2, and 14.8%, respectively; the rates for outdoor activities at these distances were 23.8, 24.5, and 13.7%, respectively (p < 0.05). After adjusting for sex, age, smoking status, family history, and smoking index, the distance of outdoor activities from busy roads was an independent risk factor for COPD. Participants whose outdoor activities were conducted <50 meters and 50–199 meters of main roads had odds ratios of 1.54 (95% confidence interval 1.01–2.36) and 1.84 (95% interval 1.23–2.76) for the risk of COPD in comparison with a distance of more than 200 meters from busy roads. Conclusions Residents of Guangzhou whose outdoor activities were close to busy roads had a high risk of COPD. Traffic-related air pollution presents a risk to human health and a risk of COPD.